Military design thinking - Jackson, Aaron P., author. Link
1 online resource.
Keywords: "This book examines the evolution of military design thinking, which is an emergent discipline within the field of military and defence studies. This discipline first emerged in the late 1990s, and its development has rapidly accelerated since the mid-2000s, in response to perceived failures of existing military doctrine and practice to adapt to the wars of the early 21st century. Initially posing a detailed critique of the shortfalls of Western strategy and operational art, and resultant military performance in places like Iraq and Afghanistan, military design thinking has since come to embrace a mixture of innovation methodologies that propose several means to overcome these shortfalls. The book features two parts, plus a comprehensive introductory chapter that summarises the field, establishes links between the two parts and discusses future research challenges. The first part, 'The Roots of Military Doctrine', discusses the epistemology and ontology of military doctrine (manuals that provide institutionally sanctioned guidance about how militaries should conduct their activities), explaining how design thinking differs radically from past military approaches to waging war. The second part, 'Design Thinking in Commerce and War', chronicles civilian and military design thinking methodologies, contrasting their paradigmatic similarities and differences and explaining what makes military design thinking a unique approach that can add value not only to military operational conduct but also potentially to a range of civilian endeavours including in business and the public sector. Together, these two sections explain the circumstances of the emergence of military design thinking as a discipline, and situate it relative to other disciplines in the fields of both military and defence studies, and design thinking. This book will be of much interest to students of military studies, security studies and International Relations, as well as military professionals"--